The role of open data in regulating combined sewer overflows - Schellart, Alma; Sharp, Liz; Bertrand-Krajewski, Jean-Luc; Rieckermann, Jörg; Anta, Jose; Blumensaat, Frank; Clemens-Meyer, Francois; Dittmer, Ulrich; Douterelo, Isabel; Gruber, Günter; Jensen, Henriette; Rokstad, Marius Møller; et al. (Water science and technology, 2025)
The aim of this work is to investigate how open data can play a beneficial role in the regulation of combined sewer overflows (CSOs). The investigation consists of a review and critical discussion of historic CSO design, alongside more recent developments of regulations and emerging experiences of monitoring CSOs and different levels of data openness. The study focuses on practice in 10 European countries/regions. The novelty of this work comes from its review of historical development of design guidelines and regulations, shifts in the aims of these regulations, practicalities around implementation and testing of compliance, alongside the openness and availability of data. The main conclusions are that increasingly complex regulation goes hand in hand with limited compliance checking and opaque decision-making, whereas opening up relatively simplistic performance data has generated public and political discussion about urban drainage systems and the potential costs of improvements in water quality of the impacted surface water bodies. Making CSO data open does, however, need to be done with due care. Collaboration with trusted citizen groups, ensuring the data are correct, easy to access, and understand, as well as avoiding a blame culture are all of key importance.